Association between glioma and neurodegenerative diseases risk: a two-sample bi-directional Mendelian randomization analysis - Liu, Yang; Chen, Youqi; Gao, Ming; Luo, Jia; Wang, Yanan; Wang, Yihan; Gao, Yu; Yang, Laiyu; Wang, Jingning; Wang, Ningxin (Frontiers in Neurology, 2024)
Earlier observational studies have demonstrated a correlation between glioma and the risk of neurodegenerative diseases (NDs), but the causality and direction of their associations remain unclear. The objective of this study was to ascertain the causal link between glioma and NDs using Mendelian randomization (MR) methodology. Methods: Genome-wide association study (GWAS) data were used in a two-sample bi-directional MR analysis. From the largest meta-analysis GWAS, encompassing 18,169 controls and 12,488 cases, summary statistics data on gliomas was extracted. Summarized statistics for NDs, including Alzheimer's disease (AD)、multiple sclerosis (MS)、amyotrophic lateral sclerosis (ALS) and Parkinson's disease (PD) were obtained from the GWAS of European ancestry. Inverse variance weighted (IVW) method was elected as the core MR approach with weighted median (WM) method and MR-Egger method as complementary methods. In addition, sensitivity analyses were performed. A Bonferroni correction was used to correct the results. Results: Genetically predicted glioma had been related to decreased risk of AD. Specifically, for all glioma (IVW: OR=0.93, 95% CI=0.90-0.96, P= 4.88×10 -6 ) and glioblastoma (GBM) (IVW: OR=0.93, 95% CI=0.91-0.95, P=5.11×10 -9 ). We also found that genetically predicted all glioma has a suggestive causative association with MS (IVW: OR=0.90, 95% CI=0.81-1.00, P=0.045). There was no evidence of causal association between glioma and ALS or PD. According to the results of reverse MR analysis, no discernible causal connection of NDs was found on glioma. Sensitivity analyses validated the robustness of the above associations. Conclusions: We report evidence in support of potential causal associations of different glioma subtypes with AD and MS. More studies are required to uncover the underlying mechanisms of these findings.